The cruel sea - Monsarrat, Nicholas 1910-1979 (Penguin Book, 2009)
Based on the author's own experiences, this book presents the story of the crew of HMS Compass Rose, a corvette assigned to protect convoys in World War Two. It offers descriptions of agonizing U-boat hunts. It tells of ordinary, heroic men who had to face a brutal menace which would strike without warning from the deep.